Women Entrepreneurship: Issues and Problems in Chandigarh & Panchkula - Sonika (Gyan Management Journal, 2021)
Background and objective: As we are living in an era of modernization and globalization, everyone wants to increase the growth and economic, social development of the country. Women entrepreneurship had been started in the USA where women had started working by themselves.  This paper has revealed the issues that are being faced by the women entrepreneurs in Panchkula & Chandigarh, which are the small cities of India.Materials and Methods: Through this paper the author wants to identify the challenges and issues faced by women entrepreneurs. The self-structured questionnaire had been designed by the authors and circulated these questionnaires to the 50 women in both cities; among them, 30 had given their responses. Data and interpretation have been done in percentage form and has shown in the form of a pie chart. Student t-test had been applied to know the difference between the different problems & different lines of activity.Result and Conclusion: This paper identified various financial, social, infrastructural problems being faced by women entrepreneurs.  It has been found that there is no difference between the problems faced by women entrepreneurs who have engaged in a different line of activity. The paper concluded that women could be encouraged for entrepreneurship and problems related to the concerned study could be minimized by taking various measures.
Keywords: Economic Development; Globalization; Issues and Challenges; Modernization; Women Entrepreneurship